Analysis of student responses toward activities using e-learning in higher education - Rini, Faiza; Pratiwi, Liani; Mary, Thomson; Weay, Ang Ling (Researcher and Lecturer Society, 2023)
The aim of this study is to investigate how students respond to learning activities using e-learning. Researchers analyzed students' responses based on four aspects of activity, including attendance discipline, assignment collection accuracy, enthusiastic use of e-learning teaching materials, and participation in group discussions. The research method used in this study is a quantitative descriptive method and usability testing method. The data analysis technique used is descriptive percentage. The sample for this study consisted of 100 students from the informatics education study program, including the batches of 2019, 2020, and 2021. The results showed that the average response rate of students towards e-learning activities was 67.19% for the year 2019, 81.32% for the year 2020, and 78.59% for the year 2021. Based on the findings, it can be concluded that students from all three batches responded positively to the e-learning activities.